2000
DOI: 10.1667/0033-7587(2000)154[0003:lcmamn]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer Mortality among Male Nuclear Workers of the Mayak Facilities in the Former Soviet Union

Abstract: An analysis of lung cancer mortality in a cohort of 1,669 Mayak workers who started their employment in the plutonium and reprocessing plants between 1948 and 1958 has been carried out in terms of a relative risk model. Particular emphasis has been given to a discrimination of the effects of external gamma-ray exposure and internal alpha-particle exposure due to incorporated plutonium. This study has also used the information from a cohort of 2,172 Mayak reactor workers who were exposed only to external gamma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
2
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 25 publications
1
18
2
1
Order By: Relevance
“…The actinides are all radioactive, and most of their isotopes decay by alpha particle emission . The densely ionizing alpha particles emitted by actinides retained in bone and liver, and in the lungs if inhaled, damage and induce cancer in those tissues in a dose-dependent manner (Finkel 1953;Jolley et al 1955;Bensted et al 1965;Levdik and Lemberg 1972;Levdik et al 1972;ICRP 1980a;Leach et al 1973; Thompson 1989;Kreisheimer et al 2000;Koshurnikova et al 2000;NCRP 2001).…”
Section: The Actinides As Health Hazardsmentioning
confidence: 99%
“…The actinides are all radioactive, and most of their isotopes decay by alpha particle emission . The densely ionizing alpha particles emitted by actinides retained in bone and liver, and in the lungs if inhaled, damage and induce cancer in those tissues in a dose-dependent manner (Finkel 1953;Jolley et al 1955;Bensted et al 1965;Levdik and Lemberg 1972;Levdik et al 1972;ICRP 1980a;Leach et al 1973; Thompson 1989;Kreisheimer et al 2000;Koshurnikova et al 2000;NCRP 2001).…”
Section: The Actinides As Health Hazardsmentioning
confidence: 99%
“…Note also that the LNT model extrapolation from high to low doses leads to phantom excess risk based on the data of Khokhryakov et al (1996)! The controls (zero-dose group) were based on national cancer statistics for the Russian population , to which some researchers have objected (Kreisheimer et al 2000). Kreisheimer et al (2000) did not find evidence for low-dose-induced protection in their study of lung cancer among Mayak workers but rather found the LNT model to describe risk adequately.…”
Section: Applications To Epidemiological Datamentioning
confidence: 99%
“…The MPA registry includes data on occupational and worker histories, results of whole body counting, radiochemical analyses of tissues, bioassays, and air sampling, and estimated internal and external radiation exposures Koshurnikova et al 1999). The MPA worker cohort is a unique source of data on high exposures to plutonium in humans and has allowed direct quantification of the plutonium dose-response functions for lung, liver and bone cancer and the proportion of cancer risk attributable to internal plutonium alpha-particle exposure (Gilbert et al 2004;Koshurnikova et al 1999;Kreisheimer et al 2000;Sokolnikov et al 2008). Epidemiologic studies have shown the risk of cancer incidence and mortality among MPA workers to be significantly related to both external and internal dose (Gilbert et al 2000(Gilbert et al , 2004Koshurnikova et al 1996;Shilnikova et al 2003;Tokarskaya et al 1995).…”
Section: Introductionmentioning
confidence: 99%